THE EFFECT PF A DIGITAL DISCHARGE EDUACATION PROGRAM ON SELF-CARE ABILITIES : A RANDOMIZED CONTROLLED TRIAL - Idealistiana, Lia; Ibrahim, Mohammad Yusof; Ramdzan, Abdul Rahman Bin (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2026)
Bakcground: Post-section cesarean patients require discharge education to follow self-care instructions, regain independence, and improve recovery. Communication methods like verbal instructions, videos, phone calls, email correspondence, websites, and mobile/tablet applications can effectively manage self-care and prevent postoperative complications.Objective: This study aimed to determine the effect of a digital discharge education program on self-care ability in women post section cesarean in Indonesia.Methods: This study was a prospective, two-arm, single-blinded randomized controlled trial at six secondary level hospitals in West Java. The study included women post section cesarean on the first day. A randomization tool was used to allocate patients in a 1:1 ratio to either interevntion or control group. Each group consisted of 120 recruited women. Therapeutic Self-Care (TSC) was used to evaluate self-care abilities. The general estimating equation is use to investigate the simple main impact of various time points within each group.Results: The repeated ANOVA test revealed that the severity of self-care ability scores increased significantly in the intervention group after intervention (p-value= 0.001). With the effect size was 0.35, indicating moderate effect size. However, control group did not show a significant improvement. The GEE analysis showed a significant effect over time on self-care ability (p=.001) and regarding the difference between the groups, the results showed significant effects on self-care ability (p=.001). The results also showed significant effects in the interaction between time and group for self-care ability.Conslusion: This study found that web-based discharge education program on self-care abilities among post C-section women in Indonesia. Future research should focus on developing innovative information technology treatments that involve healthcare consumers and practitioners to improve the delivery of prompt discharge education to general surgery patients.